Protective Effect of Procyanidin-Rich Grape Seed Extract against Gram-Negative Virulence Factors - Roberta Maria Nicolosi; Graziana Bonincontro; Elena Imperia; Camilla Badiali; Daniela De Vita; Fabio Sciubba; Laura Dugo; Michele Pier Luca Guarino; Annamaria Altomare; Giovanna Simonetti; Gabriella Pasqua (Antibiotics, 2023)
Biofilm formation and lipopolysaccharide (LPS) are implicated in the pathogenesis of gastrointestinal (GI) diseases caused by Gram-negative bacteria. Grape seeds, wine industry by-products, have antioxidant and antimicrobial activity. In the present study, the protective effect of procyanidin-rich grape seed extract (prGSE), from unfermented pomace of Vitis vinifera L. cv Bellone, on bacterial LPS-induced oxidative stress and epithelial barrier integrity damage has been studied in a model of Caco-2 cells. The prGSE was characterized at the molecular level using HPLC and NMR. The in vitro activity of prGSE against formation of biofilm of Salmonella enterica subsp. enterica serovar Typhimurium and Escherichia coli was investigated. In vivo, prGSE activity using infected Galleria mellonella larvae has been evaluated. The results show that the prGSE, if administered with LPS, can significantly reduce the LPS-induced permeability alteration. Moreover, the ability of the extract to prevent Reactive Oxygen Species (ROS) production induced by the LPS treatment of Caco-2 cells was demonstrated. prGSE inhibited the biofilm formation of E. coli and S. Typhimurium. In terms of in vivo activity, an increase in survival of infected G. mellonella larvae after treatment with prGSE was demonstrated. In conclusion, grape seed extracts could be used to reduce GI damage caused by bacterial endotoxin and biofilms of Gram-negative bacteria.